Generic versus specific sprint training in young soccer players - Jastrzebski, Z.; Radziminski, L.; Dargiewicz, R.; Jaskulska, E.; Barnat, W.; Rompa, P. (Baltic Journal of Health and Physical Activity, 2013)
Background: The aim of this study was to examine the effect of two 8-week sprint training programs on the speed and sport-specific skills of young soccer players and to determine additional effects of 8 weeks` whole body rotation.